Identifying permethrin resistance loci in malaria vectors by genetic mapping - Witzig, C.; Wondji, C.; Strode, C.S.; Djouaka, R.F.; Ranson, H. (Cambridge University Press, 2013)
Identification of the major loci responsible for insecticide resistance in malaria vectors would aid the development andimplementation of effective resistance management strategies, which are urgently needed to tackle the growing threat posedby resistance to the limited insecticides available for malaria control. Genome-wide association studies in the major malariavector, Anopheles gambiae, have been hindered by the high degree of within-population structuring and very low levels oflinkage disequilibrium hence we revisited the use of quantitative trait loci (QTL) mapping to study resistance phenotypesin this vector species. Earlier work, identified two major QTL associated with pyrethroid resistance in A. gambiae s.s. fromEast Africa using genetic crossing of laboratory-colonized resistant and susceptible strains. In this study, we report theresults from genetic mapping of pyrethroid resistance in three isofemale pedigrees established from wild-caught femaleA. gambiae s.s. mosquitoes from Benin. We identified two QTL on chromosomes 2L and 3R in these field populations, insimilar genomic locations to theQTLidentified in laboratory strains. The relative merits of two alternative study designs arediscussed and suggestions made for future genetic mapping studies of insecticide resistance in mosquitoes.